The Effect of Corporate Social Responsibility and Financial Ratios on Financial Distress - Safitri, Rissa Anie; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of Corporate Social Responsibility, Independent Board of Commissioners, Cash Flow, Profitability, and Liquidity on Financial Distress. The population in this study is all companies in the consumer non-cyclicals sector for the 2021-2023 period. A total of 14 companies were used as samples, so the number of data used was 42 observation data. Data was obtained using purposive sampling techniques and using secondary data obtained through the company's website or the Indonesia Stock Exchange website. The data analysis technique in this study is to use multiple linear regression using the SPSS statistical analysis program version 26 as a calculation tool. Based on the results of this study, Corporate Social Responsibility, Cash Flow, Profitability, and Liquidity have no effect on Financial Distress. Meanwhile, the Independent Board of Commissioners has a positive effect on Financial Distress.